1971
DOI: 10.1172/jci106536
|View full text |Cite
|
Sign up to set email alerts
|

Tension prolongation during recovery from myocardial hypoxia

Abstract: A B S T R A C T The mechanical behavior of isolated cat, rat, and dog ventricular muscle was examined during hypoxia and after reoxygenation. During hypoxia, an early abbreviation of tension duration was followed by a decline in the rate of tension development. After reoxygenation, a marked, early prolongation of tension development and relaxation time was invariably observed with little, if any, increase in peak tension. As recovery progressed, the duration of contraction gradually shortened as tension return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
1

Year Published

1978
1978
1994
1994

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(22 citation statements)
references
References 11 publications
(4 reference statements)
2
19
1
Order By: Relevance
“…The tension trace especially, which represents the final outcome of the E-C coupling process, showed a significant decrease in peak values with an abbreviated time course during hypoxia. These changes were followed by a slow recovery with a prolonged relaxation during reoxygenation (62). These findings suggest not only that our preparations were affected by hypoxia and reoxygenation but also that the subcellular functions remaining after drug intervention were much more essential as targets of hypoxia/reoxygenation than the functions deleted by it.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The tension trace especially, which represents the final outcome of the E-C coupling process, showed a significant decrease in peak values with an abbreviated time course during hypoxia. These changes were followed by a slow recovery with a prolonged relaxation during reoxygenation (62). These findings suggest not only that our preparations were affected by hypoxia and reoxygenation but also that the subcellular functions remaining after drug intervention were much more essential as targets of hypoxia/reoxygenation than the functions deleted by it.…”
Section: Resultsmentioning
confidence: 58%
“…Of interest, while the durations of Ca?' transients were abbreviated by the transition from hypoxia to reoxygenation, tension relaxation was prolonged after reoxygenation ( 19,32,62). This discrepancy between Ca?'…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the observations with low coronary flow global ischemia, hypoxia (anaerobic perfusate at control coronary flow) in this experimental model consistently caused a rise in LVEDP. This was associated with a substantial prolongation of the time constant of left ventricular relaxation, T. It is important to point out that the rise in LVEDP relative to volume, as well as the substantial prolongation of T (+300 to +500% increase) occurred during hypoxia, and within 2 min of its onset; this is distinct from the phenomenon of tension prolongation during reoxygenation following hypoxia or ischemia, as described by others (32)(33)(34). When pacing tachycardia was superimposed on hypoxia, increases in T of 500% occurred in the posttachyeardia period prior to reoxygenation, and were associated with more than a doubling of LVEDP.…”
Section: Resultsmentioning
confidence: 67%
“…Previous studies using the isometrically contracting papillary muscle preparation have reported a shortened time of relaxation associated with hypoxia (8)(9)(10). This finding is most probably a function of two factors.…”
mentioning
confidence: 83%
“…To date, however, hypoxia, a major component of the ischemic state, has not been shown to impair the relaxation of cardiac muscle (8)(9)(10).…”
mentioning
confidence: 99%